Downer, Carol (audio interview #2 of 3) - Downer, Carol (10/9/1933); Moravec, Michelle, interviewer
INTERVIEW DESCRIPTION - This second of three interviews with Carol Downer, conducted four years after the Women Rising interview, was part of a Senior Honors project at UCLA. The interview was conducted at Downer's office at the Feminist Women's Health Centers business office. This was the very first oral history interview conducted by Moravec and her own presence is notable.